Thiopurine Metabolism in the Era of Combotherapy. Issue 6 (June 2016) - Roblin, Xavier; Williet, Nicolas; Peyrin-Biroulet, Laurent
Abstract : Abstract: 6-thioguanine nucleotides levels are associated with clinical remission in patients with inflammatory bowel disease (IBD) on thiopurine monotherapy. Recently, few studies investigated the interaction between thiopurine metabolism and anti–tumor necrosis factor therapy among patients with IBD on combotherapy. Two studies demonstrated that infliximab therapy increases 6-thioguanine nucleotides level, while such effect could not be observed with adalimumab. Three studies showed that a Delta mean corpuscular volume >7 and high 6-thioguanine nucleotides levels are associated with favorable outcomes, i.e., greater mucosal healing rates, and have a positive impact on the pharmacokinetics of infliximab. These results suggest a synergistic effect between thiopurine metabolism and anti–tumor necrosis factor therapy, especially with infliximab. We propose here some algorithms for clinical practice integrating thiopurine metabolism in patients with IBD on combotherapy. Further randomized controlled trials are needed to further investigate the relationships between thiopurine metabolism and anti–tumor necrosis factor therapy and to establish the clinical utility of measuring thiopurines' metabolites in these patients in clinical practice. Whether measuring thiopurine metabolism can be used to guide decision-making in patients with IBD on combotherapy when considering drug de-escalation or discontinuation will require further investigation. Abstract : Article first published online 15 March 2016.